Load Balanced Routing for Lifetime Maximization in Mobile Wireless Sensor Networks. (15th July 2014) - Khalid, Saifullah; Masood, Ashraf; Hussain, Faisal Bashir; Abbas, Haider; Ghafoor, Abdul
Abstract : Challenge of efficient protocol design for energy constrained wireless sensor networks is addressed through application specific cross-layer designs. This design approach along with strong design assumptions limits application of protocols in universal scenarios and affects their practicality. With proliferation of embedded mobile sensors in consumer devices, a changed application paradigm requires generic protocols capable of managing greater device heterogeneousness and mobility. In this paper, we propose a novel lifetime maximization protocol for mobile sensor networks with uncontrolled mobility considering residual energy, traffic load, and mobility of a node. The protocol being generic is equally applicable to heterogeneous, homogenous, static, and mobile sensor networks. It can handle event driven as well as continuous traffic flow applications. Simulation results show that proposed scheme outperforms minimum hop routing and greedy forwarding in terms of network lifetime, data packet latency, and load balance while maintaining comparable throughput.